Analiz rezul'tatov finalov v bege na 100 m Cempionatov Mira po legkoj atletike 2015-2019 godov - Safina, R. M. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
In this article, the goal is to analyze the results of the finals in the 100 m race at the World Athletics Championships of 2015, 2017 and 2019. The dynamics of the competitive activity of short-distance runners in 2019 is compared with the results of 2015 and 2017. Using the methods of analysis of variance, using the StatPlus6 program, the significance of differences in the indicators of competitive activity was investigated. For these indicators, posterior comparisons of the results were carried out. Information obtained from the results of the competition allows coaches and athletes to ensure the stability of the level of the sports results; to outline the ways to improve the training process; to create some prerequisites for stabilizing the psychological state before responsible starts.